Paper 54: MPFL Repair has a Higher Failure Rate at Long-term Follow-up compared to MPFL Reconstruction for Recurrent Patellar Instability. Issue 7 (30th July 2022) - Wilbur, Ryan; Song, Bryant; Wasserburger, Jory; Camp, Christopher; Krych, Aaron; Stuart, Michael; Kruckeberg, Bradley
Objectives: The medial patellofemoral ligament (MPFL) is the primary soft tissue restraint to lateral patellar translation and is often disrupted with a lateral patellar dislocation. Surgical management for recurrent patellar instability focuses on restoring MPFL function with repair or reconstruction techniques. Recent studies have favored reconstruction over repair, but no long-term, comparative studies are available in the literature. Methods: A total of 55 patients (58 knees) with recurrent lateral instability were treated between 2005 and 2012 with either MPFL repair or MPFL reconstruction. Exclusion criteria included prior or concomitant tibial tubercle osteotomy or trochleoplasty, and follow-up less than 8 years. Pre- and post-operative demographic, surgical, imaging and clinical data were recorded for each patient. Results: MPFL repair was performed on 26 patients (29 knees; 14 females, 15 males) at a mean age of 19.1 years. MPFL reconstruction was performed on 29 patients (29 knees; 18 females, 11 males) at a mean age of 18.2 years. Mean follow-up was 12.0 years (range 8.3-18.9). The reconstruction group had a significantly lower rate of recurrent dislocation compared to the repair group (14% vs 41%, p=0.019) at final follow up. There were no differences in the number of pre-operative dislocations (greater than or less than 3), degree of patellar facet chondromalacia, TT-TG distance, or Tegner scores. The reconstruction group had significantly more time from injury to surgery compared to the repair group (median, 1, 460 days vs 627 days, p =0.007). There were no differences in post-operative Tegner, Lysholm or Kujala scores at final follow-up. Additionally, there were no differences in return to play rates (repair 80.8% vs reconstruction 75.0%, p=0.610) or reoperation rates (repair 20.7% vs reconstruction 13.8%, p=0.487). Conclusions: Repair of the MPFL leads to nearly 3-fold higher rate of recurrent patellar dislocation (41% vs. 14%) at long term follow-up compared to MPFL reconstruction. However, MPFL repair and reconstruction provide similar clinical results, return to play rates and reoperation rates.